Eksekusi Objek Hak Tanggungan yang Dijaminkan Kepada Pihak Ketiga Tanpa Persetujuan Kreditur - Marwa, Radisty Wensy; Susetyo, Heru (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This study intends to examine the execution of the objects of mortgages that is guaranteed under-hand to a third party without creditor’s approval. The research method used in this research is normative juridicial. There are three types of execution that are regulated in Undang-Undang Hak Tanggungan. The results of the study concluded that in terms of mortgage objects that are guaranteed under-hand to a third party, Bank Nagari gives a warning letter, legal notice, and file a lawsuit in court. That mortgages objects do not have the legal power and considered to never existed as the legal consqeunces.